ANALISIS MANAJEMEN LOGISTIK OBAT DI INSTALASI FARMASI RSUD KOTA DUMAI TAHUN 2023 - Widagdo, Fatoni; Renaldi, Reno; Rahayu, Endang Purnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on data on planning, procurement and distribution of drug logistics in 2022 obtained from the Dumai City Regional Hospital Pharmacy Installation, data on medicines realized and distributed is around 75% of the plans that have been determined, meaning that there are still around 25% of medicines that have not been realized and distributed. at Dumai City Regional Hospital. The research aims to analyze drug logistics management in the Dumai City Hospital pharmacy installation. This type of research is qualitative using descriptive analysis. There were 10 informants for this research. The research method uses interviews, observation and document tracing. The analysis technique uses data analysis triangulation. The results of the research show that drug planning in the Dumai City Hospital Pharmacy Installation has not run optimally, because the availability of human resources is still lacking. The source of the drug planning budget comes from the State budget, Revenue and Expenditure Budget Area and Regional Public Service Agency. Drug planning has been carried out according to needs, but in this planning there are obstacles, namely changes. Drug procurement in analyzing drug logistics management uses catalogs, direct procurement systems, and tender systems. Drug distribution in analyzing drug logistics management is carried out in accordance with procedures. Drug control is carried out by the activity technical executive officer who is responsible for drug logistics management activities. Keywords : Drug Logistics Management, Pharmaceutical Installation